The influence of nutrition education intervention combined with FIFA11+ program on physical fitness attributes, physical activity behaviors, eating habits and nutritional knowledge in young basketball players - Silvia Sánchez-Díaz; Javier Raya-González; Javier Yanci; Daniel Castillo (Asociación Española de Ciencias del Deporte, 2022)
The aim of this study was to analyze the effects of a nutritional education program combined with the FIFA 11+ program on physical fitness attributes, physical activity levels, food and nutritional habits and nutritional knowledge in young basketball players. Twenty-three under 14 elite basketball players (13 males and 10 females) belonging to a professional basketball academy participated in the study. Physical fitness attributes (countermovement jump [CMJ], drop jump, linear sprint, Lane Agility Drill, 505 change-of-direction, and repeated-change-of-direction [RCOD]), physical activity levels (Physical Activity Questionnaire for Adolescents, PAQ-A), eating and nutritional habits (Turconi questionnaire), and nutritional knowledge (modified version of the Turconi questionnaire) were assessed before and after the five months intervention period. Participants were involved in five nutrition education sessions and in a weekly session of the FIFA 11+ program. Pre-to-post differences revealed improvements in physical fitness attributes (i.e., CMJ, Lane Drill Test and RCOD time test [p < 0.05; effect size (ES) = 0.52 to -1.68]) and physical activity behaviors (PAQtotal and PAQ Lunch [p < 0.001; ES = 0.68-0.89]), as well as a maintenance of eating and nutritional habits and nutrition knowledge. In practical terms, the usual on-court and the implementation of nutrition education interventions combined with the FIFA 11+ improve physical fitness attributes and physical activity behaviors while favor the maintenance of eating and nutritional habits and nutrition knowledge in U14 elite basketball players.